Юридичні і нормативні аспекти перекладацької діяльності як об’єкт навчання - Ганічева, Т.В.; Ганичева, Т.В.; Ganicheva, T.V. (Харківський національний університет імені В.Н. Каразіна, Центр міжнародної освіти, 2010)
Стаття розглядає зміст формування перекладацької компетенції. Аналізуються юридичні й нормативні аспекти перекладацької діяльності.
Юридические и нормативные аспекты переводческой деятельности как объект обучения.
Legal and Normative Aspects of Interpreter’s/Translator’s Activity as the Object of Teaching
The article deals with the subject-matter of developing the interpreters’/translators’ competence. The issues concerning legal and normative aspects of the interpreter’s/translator’s activity are analyzed.
Keywords: subject-matter of interpreters’/translators’ competence development; interpreters’/translators’ competence; legal and normative aspects of interpreter’s/translator’s activity; содержание обучения будущих переводчиков; переводческая компетенция; юридические и нормативные аспекты переводческой деятельности; зміст навчання майбутніх перекладачів; перекладацька компетенція; юридичні і нормативні аспекти перекладацької діяльності